Optimal extraction conditions and quantification of lignan phytoestrogens in cereal grains using targeted LC-MS/MS - Kim, Yoonjeong; Kim, Heon-Woong; Sung, Jeehye; Kim, Younghwa (Frontiers in Nutrition, 2024)
This study aimed to optimize the extraction of lignans from cereal grains using response surface methodology (RSM). Lignans, including secoisolariciresinol (Seco), matairesinol (Mat), pinoresinol (Pin), lariciresinol (Lar), and syringaresinol (Syr), were quantified using highperformance liquid chromatography-tandem mass spectrometry. A Box-Behnken design was employed to determine the optimal values for three extraction parameters: temperature (X1: 20-60°24 C), methanol concentration (X2: 60-100%), and extraction time (X3: 30-90 min). The highest lignan contents were obtained at X1=44.24°C, X2=84.64%, and X3=53.63 min. To apply these experimental conditions to the actual experiment, the optimal conditions were slightly adjusted to X1=40°C, X2=80%, and X3=60 min. The predicted results closely matched the experimental results obtained using the modified optimal extraction conditions. The highest lignan content found in barley sprouts (85.930 µg/100 g), however, most grains exhibited relatively low concentrations of lignans. These findings provide valuable insights into the lignan content of grains and contribute to the generation of reliable data in this field.